Schroders - Roberts, Richard. author. aut Link
XXIII, 616 p.
Keywords: J.Henry Schroder Wagg & Co has been a leading merchant bank of the City of London for more than a century. This book tells its history, from its founding in 1818 by John Henry Schroder, a Hamburg merchant, through difficult times in the international slump of the early 1930s, to its rise to one of the largest and most prestigious of city firms in London today.